Conceptions of quilombola school education and the construction of the municipal curriculum reference:: some considerations - Lemos, Sara Alves da Luz; Peixoto, Ana Cristina Santos (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2021)
This paper aims to discuss Quilombola School Education as a Modality of Basic Education and its implementation in the Municipal Curriculum Framework of Aurelino Leal – BA, addressing its contributions and perspectives. This discussion arises through the process of constructing the DCRAL - Reference Curriculum Document by Aurelino Leal in 2020, in an atypical situation amid the paralysis of classes with the COVID -19 pandemic. Its construction trajectory and how Quilombola School Education enters little by little in the conquest of its rightful space and brings reflections and contributions to new hopes and perspectives in the strengthening of school education in the remaining quilombola communities, not only in the municipality of Aurelino Leal, but in each and every municipality that has remnant quilombo communities. One of these contributions is the valuation of continuing education for educators, knowing and experiencing the reality of this community, in addition to the commitment of the municipal administration regarding the implementation of DCRAL, especially on the continuing education of educators.